The Adventurers Guild - Clark, Zack Loran; Eliopulos, Nick (Disney/Hyperion, 2018)
In one of the last cities still populated after the world fell victim to monsters, Zed Kagari and Brock Dunderfel are best friends, with high hopes for the future--their plan is for Zed, with his lineage as a Freestone and half-elf, to join the Mages Guild, and for Brock to join the Merchants Guild, and together they will work to make the city thrive. All their plans are upended when they both find themselves in the Adventurers Guild instead, led by the fearsome Alabasel Frond to defend against the Dangers that threaten them all.